Does the Web of Seismic Walls Play a Role to Their Out-of-Plane Stability? - Chrysanidis, Theodoros; Tegos, Ioannis (Advanced Aspects of Engineering Research Vol. 2, 2021)
Lately, there is an international worry about the seismic behavior of structural walls, mainly concerning their lateral instability under intense seismic loading. The possibility of failure because of lateral instability is limited significantly with the proper choice of an adequate thickness. It is widely known that EC8 and the Greek Concrete Code require as a minimum thickness of shear walls 1/20 of the storey height, for walls having a rectangular section. Seismic codes, well-known and approved internationally, like the New Zealand and the American seismic code, have moved to more conservative choices concerning the minimum thickness of shear walls (1/10 of storey height the first and 1/16 the second). Flexural overstrain is the main cause that produces this lateral instability. Flexural overstrain in its turn is allowed due to the continuously increment of maximum acceptable tensile strain of steel bars. This deep excursion in the yield region of the boundary parts of shear walls increases dramatically their flexibility. At the same time these walls are liable to a reversing axial loading (tension – compression), due to seismic action and so their lateral stability is at stake. The current work dealing with these aspects is experimental and examines the influence of the web of shear walls in the halting (or not) of lateral instability.